The Hanna Farm pluton, Cobequid Highlands: petrology and significance for motion on the Kirkhill fault - Pe-Piper, Georgia; Turner, Denise (Atlantic Geology)

(untitled) (Atlantic Geoscience Society, 1988)
The Hanna Farm pluton is a complex granite - gabbro pluton which appears to be truncated by the Kirkhill fault zone, probably by predominantly dip-slip motion. A leucogranite has been intruded into the Kirkhill fault zone at the southern end of the Hanna Farm pluton. The main Hanna Farm pluton contains secondary biotite and odier evidence of hydrothermal alteration, and is petrographically and geochemically similar to a series of Early Carboniferous (ca. 345 Ma) granites in the western Cobequid Highlands. Secondary biotite within country rock has been radiomelrically dated at 303±11 Ma. The leucogranite within the Kirkhill fault zone lacks evidence of hydro thermal alteration. It shows local ductile deformation, but is not noticeably offset by the Kirkhill fault zone. The Kirkhill fault zone is one of the major east-west trending fault zones in the western Cobequid Highlands. It cuts and mylonitises late Hadrynian sedimentary and plutonic rocks, and probable Early Carboniferous plutons. The Hanna Farm pluton appears to post-date the last major phase of strike-slip motion on the Kirkhill fault